Gender Bias in China, the Republic of Korea, and India 1920-90 : Effects of War, Famine, and Fertility Decline - Gupta, Das Monica (The World Bank, 1999)
June 1999 - The proportions of girls 'missing' rose sharply in these countries during times of war, famine, and fertility decline. Resulting shortages of wives improved the treatment of adult women without reducing discrimination against daughters or increasing women's autonomy. The latter goals can be reached only with fundamental changes in women's family position-changes that are taking place only slowly. Kinship systems in China, the Republic of Korea, and North India have similar features that generate discrimination against girls, and these countries have some of the highest proportions of girls 'missing' in the world. Das Gupta and Li document how the excess mortality of girls was increased by war, famine, and fertility decline-all of which constrained household resources-between 1920 and 1990. Of the three countries, China experienced the most crises during this period (with civil war, invasion, and famine). The resulting excess mortality of girls in China offset the demographic forces making for a surplus of wives as overall mortality rates declined. India had the quietest history during this period, and consequently followed the expected pattern of a growing surplus of available wives. These changes in sex ratios had substantial social ramifications. The authors hypothesize that these demographic factors: ° Encouraged the continuation of brideprice in China, while in India there was a shift to dowry. ° Influenced the extent and manifestations of violence against women. An oversupply of women is the worst scenario for women, as there are fewer constraints to domestic violence. A shortage of women leads to better treatment of wives, as people become more careful not to lose a wife. However in situations of shortage, a small proportion of women may be subject to new types of violence such as being kidnapped for marriage.